Positive psychology the scientific and practical explorations of human strengths - Lopez, Shane J.; Pedrotti, Jennifer Teramoto; Snyder, C. R. (Sage Publications, Inc., 2019)
"Shane Lopez and Jennifer Teramoto Pedrotti offer comprehensive coverage of the science and application of positive psychology and present new frameworks for understanding positive emotions and human strengths. The authors bring positive psychology to life by tackling issues such as how positive psychology can help improve schooling and the workplace, as well as promote cooperative lifestyles among people. Further, the book covers Western and Eastern approaches to understanding human strengths, along with the cultural and developmental influences on positive functioning. The authors also explore various positive conditions such as happiness and well-being, along with other processes related to mindfulness, wisdom, courage, and spirituality"--Provided by publisher.